PENINGKATAN PRESTASI BELAJAR SISWA TENTANG MEMBACA LANCAR KALIMAT SEDERHANA MELALUI METODE DEMONSTRASI PADA KELAS I SDN 1 PEKALONGAN KECAMATAN TAMBAK KABUPATEN GRESIK - Musammah (CENDEKIA: Jurnal Studi Keislaman, 2016)
The purpose of this research is to improve student learning outcomes in reading simple sentences fluently with proper intonation. The research was conducted in the first grade at SDN 1 Pekalongan of Tambak District- Gresik totaling 12 students. This research was conducted 2 cycles using the method of demonstration. This study was conducted on 16 April 2015 until April 20, 2015 in the second semester of the school year 2014/2015. The results of the study in the first cycle showed an average achievement of students value of 67.83 and 82.17 in the second cycle of learning outcomes so that there is an increase of 14.34, while the completeness of the cycle I still reached 41.67% and the second cycle has reached 83 , 33%, so there is an increase of 41.66% completeness.